Solid particle deposition of indoor material combustion products; Process Safety and Environmental Protection; Vol. 162 - Zhdanova A. O. Alena Olegovna; Volkov R. S. Roman Sergeevich; Kuznetsov G. V. Geny Vladimirovich; Kopylov S. N. Sergey Nikolaevich; Kopylov N. P. Nikolay Petrovich; Sushkina E. Yu. Elena Yurjevna; Strizhak P. A. Pavel Alexandrovich (2022, 2022)
Title screen